Sipanje svetlobe na svetlobi - Debevc, Jernej (Matrika, 2019)
Light-by-light scattering is an interaction process predicted by quantum electrodynamics and is forbidden in the classical theory of electromagnetism. High, mostly inaccessible energies required to achieve a measurable interaction rate proved to be one of the main reasons why this process has not been experimentally confirmed even almost a century after its theoretical prediction. In 2017 the ATLAS Collaboration reported the first direct measurement of light-by-light scattering. The process and experiment performed to measure it are described in the article.
Keywords: ATLAS detector; detektor ATLAS; kvantna elektrodinamika; light-by-light scattering; quantum electrodynamics; sipanje svetlobe na svetlobi